Issue Overview - Escobar, John Willmer (Cuadernos de Administración, 2024)
This issue 79 of Cuadernos de Administración, spanning May-August 2024, is a testament to the global reach of our research. The seven published works, meeting the highest scientific and quality standards, have been contributed by authors from various countries and regions, including Colombia. These articles, spanning diverse administration topics such as marketing, public management, human talent management, finance, tourism management, sustainability, and internationalization, demonstrate the current quality of the journal's publications and their relevance on a global scale. The first article, " Systematic literature review on customer analytics capabilities" presents a systematic literature review on the topic, considering the stages of locating (identifying customers), describing (synthesizing definitions and uses of analytics in customer-related domains), deepening (identifying and interpreting common patterns in the studies), and disseminating (report preparation). It analyzes the diversity of ways to conceive analytics in organizational customer contexts based on a conceptual reference model synthesizing conceptions (action/method, complex process, or strategic resource) and roles (development of operational capabilities, dynamic capabilities, or strategic adjustment). The article " The hidden footprint of Engagement: discovering its effects on Workplace Stress and Hiding Feelings" sheds light on the practical implications of employee engagement, stress, and emotion concealment at the workplace. The results, which highlight variations based on control variables such as sector and gender, provide valuable insights for human resource management interventions and open up new avenues for research on well-being, thereby enhancing our understanding of these crucial aspects of the workplace. The article "Efficiency of public expenditure in higher education at Universidad Surcolombiana, 2016-2020" explores the analysis of public spending efficiency in a Colombian higher education institution. The study analyzed management indicators using a measurement scale for efficiency based on the resources appropriated and executed from the institution's general budget. The results indicate that the analysis of the public spending efficiency indicator in higher education achieved positive efficiency due to a good balance of public finances, installed capacity growth, laboratory acquisition, increased intellectual production among teachers and students, and strengthening of student welfare. An analysis of share issuance conducted by Mexican companies listed on the Mexican Stock Exchange (BMV) during 2012-2022 is explored in the article " Current paradigm of corporate governance and determinants of share issuance by Mexican companies" The study aims to determine whether Mexican companies maintain the corporate control paradigm by holding the most significant percentage of shares among family members and their close circle. Additionally, company age, sales level, and economic sector were evaluated. The results show no evidence to determine that the paradigm has changed. The article "Analysis of the Gastronomic Tourism Potential in the La Candelaria locality, Bogotá" diagnoses the gastronomic situation in a locality of Colombia's capital. It uses a qualitative methodology, starting with an analysis of the territorial and tourism context and the supply, demand, potential, and trends in gastronomic tourism following the UNWTO and the Basque Culinary Center proposal. The results confirm a value chain in gastronomic tourism in the region, which must be enhanced through joint actions between the government and gastronomic establishments. The article "Green business strategy and ecoinnovation in manufacturing companies; effects on environmental performance" mentions that the sustainable business strategy (ENS) maintains significant relationships regarding types of eco-innovation, encompassing activities in products, processes, and organization that contribute to achieving environmental performance within the Mexican manufacturing industry. This study emphasizes the essential role of the ENS as a facilitator of eco-innovation activities in the manufacturing industry. Finally, the last reflection article considers relevant topics related to the internationalization of a business group in Latin America, "Evolution of INDITEX group’s internationalization strategy in Latin America" This work analyzes the internationalization strategies applied in a sustained expansion process, focusing on the global positioning of the group at various levels (competition, commercial development, logistical development, delocalization strategies, etc.), seeking to investigate the possible maneuvers undertaken over the years, with a particular focus on Latin America. This region presents its own instabilities and unique characteristics in each country, as well as differences in market demand. The publication of issue 79 of the Journal Cuadernos de Administración of the Universidad del Valle's Management Sciences Faculty is a testament to the collective academic effort that has gone into this issue. We, as a prestigious journal in the scientific dissemination of knowledge in various areas, would like to express our gratitude to each of the authors of these seven articles and the peer reviewers who have supported the editorial process. It is through such collaborative efforts that we continue to advance our understanding in the field of administration and management studies.